Analisis Kepuasan Pengguna Terhadap e-Learning Moodle Berbasis Web Dengan Menerapkan Metode SUS - Guidio Leonarde Ginting; Natalia Silalahi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Research on measuring LMS user satisfaction has been widely conducted; however, there remains a gap in the comprehensive evaluation of e-learning system usability, particularly in the context of Moodle platform adaptation in Indonesia. This study adopts a more systematic approach by employing the System Usability Scale (SUS) as the primary measurement instrument, complemented by qualitative analysis to provide a deeper understanding of the usability aspects that need improvement. The research employs a quantitative approach using survey methods to analyze user satisfaction with Moodle-based e-learning systems. This quantitative approach was chosen as it allows systematic measurement of the system's usability using the standardized System Usability Scale (SUS) instrument [12]. Several stages are involved in this study, including pre-research, instrument preparation, validity and reliability testing, data collection, and data analysis. Given the highly fluctuating and difficult-to-determine population size, the study uses snowball sampling to obtain the sample. The respondents include active university students from various higher education institutions in Indonesia who regularly use the Moodle platform for their learning activities. Other inclusion criteria include: having used Moodle for at least one semester, actively participating in online learning, and being willing to complete the questionnaire. The significance of this research lies in its contribution to generating empirical data on the usability of Moodle-based e-learning systems using the standardized SUS method. The results are expected to provide practical recommendations for improving system usability while enriching the literature on the implementation of SUS in the e-learning context in Indonesia.